Smart i-Bot / Nur Amerah Azeerah Mohd Zaidon, Siti Nadhirah Mohd Shaufi … [et al.] - MOHD ZAIDON, NUR AMERAH AZEERAH; MOHD SHAUFI, SITI NADHIRAH; MAHYUDIN, NUR AISHAH; BERD, EMILY CHRIST; MOHD AZAHAR, PUTRI NATASHA AQILAH (2018)
The product is known as Smart i-Bot. Smart i-Bot is a small, light and portable auto mobilize appliance that is used for air purifying inside the building using activated carbon. It comes with beeper that assist the Smart i-Bot to detect the presence of allergen, dust and pollutant at particular spaces. Apart from functioning as air purifier, Smart i-Bot also acts as security camera that can be directly send the real-time or recorded footage of security camera as well as the data of air quality performance to the mobile phones using Wi-Fi connection. Itis also a self-rechargeable appliance where it will recharge itself when the battery is low.